DRY PORT BUSINESS DEVELOPMENT STRATEGY - Jourdan, Michael; Harianto, Harianto; Hakim, Izzuddin A (Jurnal Aplikasi Manajemen, 2018)
Export and import activities are the most important part of economic activity in Indonesia. These need to be supported by good port infrastructure. Cikarang Dry Port (CDP) as the only Dry Port, owned by private, should be able to support export and import activities and supply chains, especially in the Greater Jakarta and Cikarang areas. There is a need to develop appropriate business development strategies to maximize resources and optimize opportunities from the CDP business environment. These study aims were identifying the influence of internal and external factors that affect the development of the CDP business and formulating business development strategies. The method used in this study is descriptive analysis and purposive sampling. Analytical tools used include internal and external analysis and SWOT. The main strength is the availability of land port capacity. An external factor that provides relative significance to the successful development of Dry Port is the usage of internet and application on a smartphone. The regulation for expansion and New Priok business development by JICT which is the biggest threat scored. Future research is expected to analyze the efficiency of time, performance and human resources in Cikarang Dry Port.